Ketahanan Ekonomi Rumah Tangga Pedagang Kaki Lima DKI Jakarta di Masa Pandemi Covid-19 - Beti Nurbaiti, Beti Nurbaiti; Kemas Ridwan K, Kemas Ridwan K; Siscawati, Mia; Chotib, Chotib; Allo, Elisabeth Ratu (Jurnal Keamanan Nasional, 2021)
This study is to aiming the economic resilience of street vendors or Pedagang Kaki Lima (PKL) during the Covid-19 pandemic condition at DKI Jakarta. Economic resilience is one of the important aspects of actualizing economic resilience. PKL that has resilience can drive the national economy through the informal sector, otherwise, if it happens, it will become the burden of the city itself. The fragility of national security will threaten citizen’s safety and convenience. This study uses quantitative approach with the primer data from 1420 respondents PKL of study masterplan PKL DKI Jakarta in 2021. PKL is scattered in five areas in DKI Jakarta, most of the respondents are migrants or immigrants who have been living in DKI Jakarta for a long time. Result of this study is showing that social capital helps street vendors to survive, especially during the COVID-19 pandemic in obtaining loans without access to formal financial institutions. Social capital among street vendors saves them from falling into the trap hole, threatened with being homeless and beggars. They help each other among street vendors in terms of finance used for daily household needs as well as for trading capital. Social capital in the form of a sense of community and solidarity as well as mutual as a basis have trust among street vendors have become a factor in their economic resilience household, especially in these difficult times.